OPTIMIZATION OF NARRATIVE WRITING LEARNING THROUGH COMMUNICATIVE MEDIA IN DEAF STUDENTS IN GRADE VII JUNIOR HIGH SCHOOL - Sriwidiastuty, Asi; Rokhman, Fathur; Wagiran, Wagiran; Hartono, Hartono (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to examine the optimization of serial image media as an effective communicative tool for enhancing narrative writing skills among deaf students, addressing the challenges posed by limited language development and auditory impairments. Methods: A literature review approach was employed, analyzing 15 peer-reviewed articles published between 2018 and 2024. Articles were identified using targeted keywords such as